Predictors of insecticide-treated net utilization among children under age 5 in refugee settlements in Uganda: analysis of the 2018-19 Uganda malaria indicator survey - Semakula, Henry Musoke; Mugagga, Frank (DHS Working Papers No. 206, 2024)
BACKGROUND: The World Health Organization has identified the use of insecticide-treated nets (ITNs) as an effective approach for malaria prevention. Despite the distribution of ITNs by the Government of Uganda to refugees, malaria is among the key causes of mortality and morbidity among children under age 5 in refugee settlements. There are persistent challenges and complexities in malaria control and prevention efforts in these settings. By addressing the unique challenges faced by refugees in using ITNs for their children under age 5, we can make significant strides toward achieving malaria control and improving the health and well-being of children in refugee settlements.